Estudo da eficiência de coleta e queda de pressão para ciclones a gás alimentados com finos de xisto - Frare, Laercio Mantovani (1999)
The effect of solids loading and feed velocities on the pressure drop and overall collection efficiency of cyclone were studied. To carry out the present work, it was built an small scale equipment composed by a cyclone, a fan, a feeding system, a dust hopper and pressure measuring. Two cyclones were used: a high efficiency Stairmand prototype and Lapple type. Both having an internal cylinder diameter of 20,6 cm. Experiments were carried out using oil shale particles, from PETROSIX/PETROBRAS, with density 2,0371 g/cm3 and diameter less then 74μm The solid's loading ranged from 0,001 to 0,025 kg/m3 and gas velocities between 12 and 17,4 m/s. The experiments results have shown the overall collection efficiency in both cyclones types to be independent of solid's loading and gas velocities, under the conditions studied. The pressure drop experimental results obtained, without presence of particles, were best fitted with models proposed by : CASAL and MARTÍNEZ-BENET, (1983), and CREMASCO and NEBRA, (1992). Results have demonstrated that, even for low particle concentration in the feed, the pressure drop was lower than that caused by air (gas phase) in absence of particles. It was observed a decrease in the pressure drop with the increase of solids loading in the range of conditions studied. A satisfactory fitting of pressure drop results was obtained with models including presence of particles in the gas phase. The results have also demonstrated that the inclusion of dust collection system (dust hopper) decreases the gas pressure drop in the cyclone.